Investigation of the quantitative and qualitative shipping market research and forecasting methods and their strategic applications to liner shipping and tramp shipping (VLCC sector) - Xia, Wen (2009)
This paper conducts an extensive Literature Review of the most commonly used quantitative and qualitative forecasting methods both in general and in shipping. Four forecasting methods – Exponential Smoothing, Multiple Regression, ARIMA, and Simple Average Combined Forecast – will be carried out to forecast the average earnings for an early 1990s built VLCC from January to August 2008 based on the historical data from March 1991 to December 2007. The four methods will then be compared by using four accuracy measures. We will conclude that Simple Average Combined Forecast is the best of the four methods in this task. The forecast results prove to be sufficiently reasonable, and can be a great help to VLCC shipping companies in their strategic decision-making.